Inhibin-betaC subunit expression in normal and pathological human placental tissues - Mylonas, Ioannis; Makovitzky, József; Kunze, Susanne; Brüning, Ansgar; Kainer, Franz; Schiessl, Barbara (Systems biology in reproductive medicine, 2011)
Inhibins and activins are important regulators of the female reproductive system. Recently, a novel inhibin betaC subunit has been identified. However, only limited data on the expression of this novel inhibin-betaC subunit in normal and pathological human placentas exist. Tissue specimens of normal, preeclamptic, hemolysis, elevated liver enzymes, low platelets (HELLP), and intrauterine growth restriction (IUGR) pregnancies (n = 24) were obtained at the conclusion of a cesarean section. Normal and pathological placental tissues were analyzed by an immunohistochemical staining reaction with a specific antibody against this novel inhibin-betaC subunit. Overall, expression of the inhibin-betaC subunit could be demonstrated in normal and pathological placental tissue. The immunoreactive score (IRS) for inhibin-betaC did not show any significant differences between normal, preeclamptic, HELLP, and IUGR tissue in extravillous trophoblast and syncytiotrophoblast cells. Immunolabelling of this novel inhibin-βC protein in normal and pathological placental tissue was demonstrated, although no differences in the staining intensity could be observed. Therefore, the inhibin-βC isoform might not primarily be involved in the pathogenesis of these pregnancy-associated disorders. The functional role of this novel inhibin-betaC subunit in normal and pathological human placenta is still quite unclear and should thus be further investigated.